Pertumbuhan, Produksi dan Kandungan Triterpenoid Dua Jenis Pegagan (Centella asiatica L. (Urban)) Sebagai Bahan Obat pada Berbagai Tingkat Naungan - Ani Kurniawati; Latifah K. Darusman; Rani Yulie Rachmawaty (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
The research was aimed to determine the optimum shading level and effect two types of Indian Pennywort (Centella asiatica L. Urban)) on growth, production, and triterpernoid. The research was conducted on March until November 2004 at BIOFARMAKA Research Station, Darmaga and chemical analysis was conducted at Analytical Chemistry Laboratory, FMIPA, Baranangsiang. Split plot design with two factors was used in this experiment. The first factor was shading level as main plots consisting of 0, 25, 55, and 75% shading level. The second factor was type of Indian Pennywort as subplots consisting of big and small Indian Pennywort. Result of the reseach showed that shading effects decrease leaf area indeks, yield, and composition of triterpenoid content of Indian Pennywort. No shading treatment showed optimum growth and yield. The combination of 25% shading and small type of Indian Pennywort gave the highest triterpenoid content. Both types of Indian Pennywort showed best growth; the difference in length of petiole, number of leaf and shoots but the small one gave the best yield. Key words : Indian Pennywort type, shading level, triterpenoid